Analisis Strategi Bauran Promosi terhadap Volume Penjualan Restoran XYZ - Megalia, -; Sumarwan, Ujang; Saptono, Imam Teguh (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2017)
This study examines the strategic influence of promotion mix on the volume of aggregation and to know whether the marketing mix run by the Restaurant XYZ affect consumer spending. The theory used in this research is the promotion mix. The research design was conduced with a quantitative descriptive approach through an interview using quisionaire. Sampling method used is a purposive sampling technique with the number of respondents counted 200 people. In this study measure the influence caused by the promotion mix variables such as advertising, personal selling, sales promotion, public relations, and direct selling to increase sales volume. The results show that advertising variables are the most influential variabel of sales volume and the promotion mix simultaneously influences the buying decision of the customer. The findings of this research provide managerial implications that restaurant should not only focus on promotions costs for advertising alone, but also need to pay close attention to the allocation of appropriate funds to see the effectiveness of increased sales volume.